ANALISIS KREATIVITAS MUSIKALISASI PUISI MELALUI MODEL COOPERATIVE LEARNING OLEH SISWA KELAS XI DI SMA NEGERI 1 DARUL HASANAH - Ardila Wahyuni; Lusi Selvia Fitri; Rekaza Akbar (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this study was to describe the results of poetry musical creativity through the STAD (Student Team Achievement Divisions) cooperative learning model at SMA Negeri 1 Darul Hasanah. The method used is descriptive method taken from the type of qualitative research. The population in this study was the entire class XI totaling 35 students, while the sample in this study was class XI IPS which amounted to 10 students at SMA Negeri 1 Darul Hasanah. Data collection techniques include primary data consisting of performance, interviews, and observations, while secondary data is only documentation. The data analysis technique uses the arithmetic average formula to calculate the results of the performance and uses an assessment rubric, while the observation uses the percentage formula. The results of the research found in the field that the application of the cooperative learning model can provide quite good cooperation results even though some students are less willing to follow the directions of the teacher so that the results of their work are classified as poor. The results of the poetry musicalization which started with the preparations made by the students were good by preparing chord accompaniment instruments such as guitar and percussion including: two buckets and one aqua bottle filled with sand. Then the preparation of poetry readers is read by two people in turn and has prepared four singers to bring up the musicalization of their poetry which is sung in certain parts. The incubation process or the designing process is good because they have compiled the poem in advance along with the selection of the right song according to the title of the poem and the guitar music accompaniment is good, but the percussion pattern is still lacking but is covered by the ability of singers, poetry readers, and guitar players who are good at it. good. The process of special illumination for percussion is still lacking because their practice is not too serious so that the results shown from the journey of musical poetry are not good. However, the vocal players, both poetry readers and singers, still maintain their tune or pitch well so that they are slightly covered from mistakes made by percussionists. The verification stage that has been described previously can be concluded that the performance of the poetry musical has a poor tempo while the guitar accompaniment is quite good, but the vocals are good in conveying the interpretation so that holistically the work is quite good for a beginner.